Production of 3-Hydroxypropionaldehyde from Glycerol - Slininger, Patricia J. (1983)
3-Hydroxypropionaldehyde is a precursor to acrolein, which can be used as an intermediate for making acrylic acid and a variety of other useful industrial chemicals. Conversion of glycerol, a renewable resource, to 3-hydroxypropionaldehyde was attempted via action of glycerol dehydrase isolated from Lactobacillus sp. strain NRRL B-1720. This method, however, was unsatisfactory because enzyme activity was lost within 60 to 90 min after the reaction initiation. Fermentation of glycerol by whole cells of Klebsiella pneumoniae NRRL B-199 in the presence of optimal semicarbazide hydrochloride proved more effective. Using this technique, glycerol solutions of 30 g/liter yielded 3-hydroxypropionaldehyde solutions of 13.1 g/liter. Thus, a conversion efficiency equal to 55% of the theoretical maximum was realized.